2021
DOI: 10.1002/anie.202111855
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal Ligation‐Activated Fluorogenic FRET Dyads

Abstract: An energy transfer-based signal amplification relay concept enabling transmission of bioorthogonally activatable fluorogenicity of blue-excitable coumarins to yellow/red emitting cyanine frames is presented. Suchr elay mechanism resulted in improved cyanine fluorogenicities together with increased photostabilities and large apparent Stokes-shifts allowing lower background fluorescence even in no-wash bioorthogonal fluorogenic labeling schemes of intracellular structures in live cells.These energy transfer dyad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…In 2022, Albitz et al demonstrated that bio-orthogonal ligation could be harnessed to activate FRET dyads via manipulating the quenching effect of tetrazine in the FRET pair . In the preactivated FRET pair, coumarin–tetrazine and Cy5 were conjugated into one molecule.…”
Section: In Vivo Imaging With Bio-orthogonal Ligationmentioning
confidence: 99%
“…In 2022, Albitz et al demonstrated that bio-orthogonal ligation could be harnessed to activate FRET dyads via manipulating the quenching effect of tetrazine in the FRET pair . In the preactivated FRET pair, coumarin–tetrazine and Cy5 were conjugated into one molecule.…”
Section: In Vivo Imaging With Bio-orthogonal Ligationmentioning
confidence: 99%
“…Besides the good biocompatibility of CPs modified with tetrazine groups, it can also be designed as turn-on fluorescence probe. 71 The tetrazine groups as energy acceptors can receive the energy given by the CPs so that the fluorescence of the CPs is quenched. However, when tetrazine groups react with TCO, the fluorescence signals of conjugated systems were recovered.…”
Section: Selective Responses Of Cpsmentioning
confidence: 99%
“…Arguably, the most important example of this concept is tetrazine (Tz) probes, which gained popularity due to their fast reactivity via inverseelectron-demand Diels-Alder cycloaddition reaction. [28][29][30][31][32][33][34][35][36][37][38] Tz has been shown to quench fluorescence via various photophysical mechanisms, including Forster resonance energy transfer (FRET), 39,40 through-bond energy transfer (TBET), 26,27 Dexter-type electron exchange, 41 and photoinduced electron transfer (PET). 42 Over the last few years, a range of design strategies has been investigated in collaboration with different fluorophore scaffolds to harness various Tz-mediated quenching mechanisms and achieve fluorogenic tetrazine probes extending up to the far-red/NIR range.…”
Section: Introductionmentioning
confidence: 99%
“…42 Over the last few years, a range of design strategies has been investigated in collaboration with different fluorophore scaffolds to harness various Tz-mediated quenching mechanisms and achieve fluorogenic tetrazine probes extending up to the far-red/NIR range. 26,27,30,[33][34][35][36][37][38][39][40][41][42] While such fluorogenic probes have been promising, the quenching strategies are not generalizable to diverse libraries of fluorophore families, requiring extensive design efforts to customize quenching mechanisms for each fluorophore scaffold. In addition, access to these fluorogenic probes often requires direct alteration of the core fluorophore skeleton, demanding re-optimization of the laborious fluorophore synthesis scheme and tackling critical synthetic challenges.…”
Section: Introductionmentioning
confidence: 99%